A correlation study between meteorological parameters and COVID-19 pandemic in Mumbai, India. Issue 6 (November 2020) - Kumar, Gaurav; Kumar, Ritu Raj
Abstract: Background and aims: Meteorological parameters play a major role in the transmission of infectious diseases such as COVID-19. In this study, we aim to analyze the correlation between meteorological parameters and COVID-19 pandemic in the financial capital of India, Mumbai. Methods: In this research, we collected data from April 27 till July 25, 2020 (90 days). A Spearman rank correlation test along with two-tailed p test and an Artificial Neural Network (ANN) technique have been used to predict the associations of COVID-19 with meteorological parameters. Results: A significant correlation of COVID-19 was found with temperature (Tmin ), dew point (DPmax ), relative humidity (RHmax, RHavg, RHmin ) and surface pressure (Pmax, Pavg, Pmin ). The parameters which showed significant correlation were then taken for the modeling and prediction of COVID-19 infections using Artificial Neural Network technique. Conclusions: It was found that the relative humidity and pressure parameters had the most influencing effect out of all other significant parameters (obtained from Spearman's method) on the active number of COVID-19 cases. The finding in this study might be useful for the public, local authorities, and the Ministry of Health, Govt. of India to combat COVID-19. Highlights: The impacts of meteorological factors on COVID-19 case counts were assessed. Temperature, Dew Point, Relative Humidity, and Surface Pressure showed positive significant associations. COVID-19 displayed negative associations with Wind Speed and Absolute Humidity.